1994
DOI: 10.1002/ajmg.1320490211
|View full text |Cite
|
Sign up to set email alerts
|

Polydactyly, campomelia, ambiguous genitalia, cystic dysplastic kidneys, and cerebral malformation in a fetus of consanguineous parents: A new multiple malformation syndrome, or a severe form of oral–facial–digital syndrome type IV?

Abstract: We describe a 27-week fetus with occipitoschisis, polydactyly, campomelia, cleft palate, laryngeal dysplasia, ocular colobomata, hepatic fibrosis and intrahepatic cyst, ambiguous genitalia, cystic dysplastic kidneys, and brain malformation. This pattern of abnormalities appears unique. The differential diagnosis is discussed. The parents are first cousins, making autosomal recessive inheritance likely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…For example, cardiac malformations have been described in several types of OFD syndrome [16,19,28]. Ades et al [29] reported a fetus with severe malformations of the kidneys, heart, hepatic ducts, lung and ambiguous genitalia. Cases of OFD with multiple skeletal and visceral involvement were also described [5,17,20,27,3034].…”
Section: Discussionmentioning
confidence: 99%
“…For example, cardiac malformations have been described in several types of OFD syndrome [16,19,28]. Ades et al [29] reported a fetus with severe malformations of the kidneys, heart, hepatic ducts, lung and ambiguous genitalia. Cases of OFD with multiple skeletal and visceral involvement were also described [5,17,20,27,3034].…”
Section: Discussionmentioning
confidence: 99%
“…Given this complex group of conditions, what is the purpose of attempts at classification? Although many of these conditions are autosomal recessive, such as classic OFDS IV and the OFDS described by Chitayat et al [1992] and present in our patients 4 and 5, OFDS VIII is X-linked recessive, Pallister-Hall syndrome is likely autosomal dominant [Donnai, 1993], and the ''lethal'' OFDS in Table III has an unknown mode of inheritance (although parents were consanguineous in the report of Ades et al, 1994). Thus an accurate diagnosis is essential for precise appraisal of recurrence risks.…”
Section: Discussionmentioning
confidence: 89%
“…Additional patients stated to have Mohr-Majewski ''compound,'' or OFDS IV, include those described by Meinecke and Hayek [1990], Gillerot and Koulischer [1988], Ades et al [1994], and Silengo et al [1987]. The patients of the first three reports had tibial defects; those of the fourth did not.…”
Section: Discussionmentioning
confidence: 99%
“…This patient was diagnosed prenatally by sonography as possible OFDS IV. Ades et al [15] reported on a 27-week-old fetus with possible OFDS IV with ambiguous genitalia. Yildirim et al [ Excision of the extra digits and reconstruction of the syndactyly.…”
Section: Discussionmentioning
confidence: 98%